Is There a Relationship Between Bovine Tuberculosis (bTB) Herd Breakdown Risk and Mycobacterium avium subsp. paratuberculosis Status? An Investigation in bTB Chronically and Non-chronically Infected Herds - Byrne, Andrew W.; Graham, Jordon; Milne, Georgina; Guelbenzu-Gonzalo, Maria; Strain, Sam (Frontiers in Veterinary Science, 2019)
Background Bovine tuberculosis (bTB; Mycobacterium bovis) remains a significant problem in a number of countries, and is often found where M. avium subsp. paratuberculosis (MAP) is also present. In the United Kingdom, bTB has been difficult to eradicate despite long-term efforts. Co-infection has been proposed as one partial mechanism thwarting eradication. Methods A retrospective case-control study of 4500 cattle herds in Northern Ireland, where serological testing of cattle for MAP, was undertaken (2004-2015). Blood samples were ELISA tested for MAP; infection of M. bovis was identified in herds by the comparative tuberculin test (CTT) and through post-mortem evidence of infection. Case-herds were those experiencing a confirmed bTB breakdown; control-herds were not experiencing a breakdown episode at the time of MAP testing. A second model included additional testing data of faeces samples (culture and PCR results) to better inform herd MAP status. Multi-level hierarchical models were developed, controlling for selected confounders. A sensitivity analysis of the effect of MAP sample numbers per event and the prior timing of tuberculin-testing was undertaken. Results 45.2% (n=250) of case observations and 36.0% (3,480) of control observations were positive to MAP by ELISA (45.8% and 36.4% when including ancillary faecal testing, respectively). Controlling for known confounders, the adjusted odds ratio (aOR) for this association was 1.339 (95%CI:1.085-1.652; including ancillary data aOR:1.356;95%CI:1.099-1.673). The size-effect of the association increased with the increasing number of samples per event used to assign herd MAP status (aOR:1.883 at >2samples, to aOR:3.863 at >10samples), however the estimated CI increased as N decreased. 41.7% of observations from chronic herds were MAP serology-positive and 32.2% from bTB free herds were MAP positive (aOR: 1.170; 95%ci: 0.481-2.849). Discussion Cattle herds experiencing a bTB breakdown were associated with increased risk of having a positive MAP status. Chronic herds tended to exhibit higher risk of a positive MAP status than bTB free herds, however there was less support for this association when controlling for repeated measures and confounding. MAP co-infection may be playing a role in the success of bTB eradiation schemes, however further studies are required to understand the mechanisms and to definitively establish causation.